An effective approach of vapour assisted morphological tailoring for reducing metal defect sites in lead-free, (CH3NH3)3Bi2I9 bismuth-based perovskite solar cells for improved performance and long-term stability - Sagar Jain (Nano Energy, 2018)
We present a controlled, stepwise formation of methylammonium bismuth iodide (CH3NH3)3Bi2I9 perovskite films prepared via the vapour assisted solution process (VASP) by exposing BiI3 films to CH3NH3I (MAI) vapours for different reaction times, (CH3NH3)3Bi2I9 semiconductor films with tunable optoelectronic properties are obtained. Solar cells prepared on mesoporous TiO2 substrates yielded hysteresis-free efficiencies upto 3.17% with good reproducibility. The good performance is attributed mainly to the homogeneous surface coverage, improved stoichiometry, reduced metallic content in the bulk, and desired optoelectronic properties of the absorbing material. In addition, solar cells prepared using pure BiI3 films without MAI exposure achieved a power conversion efficiency of 0.34%. The non-encapsulated (CH3NH3)3Bi2I9 devices were found to be stable for as long as 60 days with only 0.1% drop in efficiency. This controlled formation of (CH3NH3)3Bi2I9 perovskite films highlights the benefit of the VASP technique to optimize material stoichiometry, morphology, solar cell performance, and long-term durability.